Associations of Hemodynamic Load and Ventricular Repolarization in Patients With Newly Diagnosed Essential Hypertension: A Long‐Term Follow‐Up Study. Issue 3 (12th March 2014) - Antonakis, Velissaris; Tsioufis, Costas; Tsiachris, Dimitris; Andrikou, Ioannis; Fantaki, Maria; Dagres, Nikos; Vrachnis, Nikos; Stefanadis, Christodoulos
<x xml:space="preserve">Abstract</x> The evolution of QT interval and its dispersion (QTd) were studied in 135 newly diagnosed nondiabetic patients, as well as the relationship between changes of these left ventricular (LV) repolarization parameters with blood pressure (BP) and LV mass changes, which were prospectively studied for a median period of 3.8 years. At baseline and at last follow‐up visit, all patients underwent ambulatory BP monitoring, echocardiographic assessment, and 12‐lead electrocardiography. At the end of follow‐up, responders of antihypertensive treatment based on a reduced 24‐hour systolic BP (n=122) exhibited a reduction in LV mass index (by 7.6 g/m2, P<.001) and corrected QT (by 4.3, P=.038), while corrected QTd was unchanged. In nonresponders (n=13), although no difference in LV mass index was observed, corrected QT increased by 12.4 ms (P=.048) and corrected QTd by 8.2 ms (P=.027). Changes in parameters of LV repolarization were related to BP changes but not to changes of myocardial size.